CLINICAL STUDY TO EVALUATE AND COMPARE THE EFFICACY OF TWO AYURVEDIC TREATMENT REGIMENS INCLUDING CYATHULA PROSTRATA AND ACHYRANTHES ASPERA IN MANAGING BLEEDING PILES - D.P.A.Dissanayake; S.Sivaganesh; M.H.A.Tissera; S.M.Handunnetti (International Journal of Ayurveda and Pharma Research, 2019)
Background: Sri Lankan Ayurveda physicians mostly recommend Rathkaralheba (Cyathula prostrata) decoction as a treatment for Sraviarshas (bleeding piles) while some patients use Gaskaralheba (Achyranthes aspera) as it is available everywhere. This study was planned to evaluate the effectiveness of two Ayurvedic regimens including Rathkaralheba and Gaskaralheba. Methods: 100 patients with bleeding piles randomly allocated into two groups. Patients of Group A and B were given treatment regimen A and B respectively. Treatment regimen A contained Gaskaralheba decoction, Thriphala tablets and sitz bath. Treatment regimen B included Rathkaralheba decoction, Thriphala tablets and sitz bath. Duration of the treatment was two weeks. Eight clinical parameters relating to bleeding piles were monitored. Results: Data collected from 92 cases (46 cases in each group) were analyzed. The study results showed that statistically highly significant reduction (p<.001) of bleeding, pain and constipation in both groups. Size of the mass has significantly reduced (p<.05) in both groups. In group A, itching was reduced significantly (p<.05) and reduction of prolapse was not significant. In group B, prolapse was reduced significantly (p<.05) but itching was not reduced significantly. Conclusion: Both treatment regimens A and B were found to be equally effective in the treatment of Sraviarshas specially reducing the symptoms of bleeding, pain and constipation